Determinants of e-government services adoption in Pakistan: an integrated model. (2013) - Azam, Afshan; Qiang, Fu; Abdullah, Muhammad Ibrahim
The purpose of this paper is to develop a model that can explain the determinants of e-government in Pakistan. This paper develops an integrated model by using Unified Theory of Acceptance and Use of Technology (UTAUT) and initial trust and outlines the factors corroborating the adoption of e-government services in Pakistan. Two paths multiple regressions were used on a sample of 400 university students. The analysis shows that performance expectancy, social influence and initial trust positively influence the behaviour intention to use e-government services. Trust of the internet and trust of the government are found to significantly predict initial trust on e-government services. The integrative model is of value for e-government decision makers to induce citizens to adopt e-services of government in developing countries like Pakistan. To date, this is the first research that has been conducted to analyse factors which determine the adoption of e-government in Pakistan.